The Effect of The Consumers’ Increasing Interest in Shopping on Shopee During the Pandemic Era - Muh. Iqbal Sitompul; Nuri Aslami (International Journal Labs, 2022)
This research aims to identify, analyze and find out how the influence of increased consumer shopping interest in Shopee during pandemic times. The research method used is a quantitative descriptive research method. The data collection technique used is a questionnaire technique that is distributed in the form of g-form online with 30 respondents divided into women 20 people and men 10 people and with online interview techniques through electronic media with 2 randomly selected sources. The results of online surveys and interviews are analyzed and interpreted narratively. The results showed that the increased interest in shopping consumers at Shopee during the pandemic was influenced by prices, ease of transaction, confidence level, advertising, attractive promos offered and many payment systems offer to choose from.